Off-shoring and productivity growth in the Italian manufacturing industries - Francesco Daveri; Cecilia Jona-Lasinio (Center for Economic Studies and ifo Institute (CESifo), 2008)
We study the relation between the off-shoring of intermediates and services and productivity growth in the Italian manufacturing industries in 1995-2003. Our results indicate that the off-shoring of intermediates within the same industry (narrow off-shoring) is beneficial for productivity growth, while the off-shoring of services is not. We also find that the way in which off-shoring is measured may matter considerably. The positive relation between off-shoring of intermediates and productivity growth is there with our direct measures based on input-output data but disappears when either a broad measure or the Feenstra-Hanson off-shoring measure employed in other studies are used instead.
Keywords: F16; F23; O4; 330; offshoring; productivity; growth; Italy; manufacturing; decline; Offshoring; Verarbeitendes Gewerbe; Produktivität; Auslandsproduktion; Vorprodukt; Unternehmensdienstleistung; Italien